Pengembangan Media Pembelajaran Pendidikan Agama Islam Materi Tata Cara Wudhu Berbasis Vidio Visual pada Siswa Kelas II SD Terpadu Ainul Ulum - Oga Sugianto (Social Science Academic, 2023)
The objectives in this ilmianh paper are: 1) To find out how to develop learning media for ablution procedures based on visual videos in grade II students of SD Terpadu Ainul Ulum Pulung. 2) To find out how the validity of learning media ablution procedures based on visual videos in grade II students of SD Terpadu Ainul Ulum Pulung. 3) To find out how effective the learning media for ablution procedures is based on visual videos in grade II students of SD Terpadu Ainul Ulum Pulung. Research methods: Research & Development (R&D). To develop products using a 4-D development model consisting of four stages: define, design, develop, and disseminate. In the study, only three stages were carried out, namely to the development stage because of limited time and cost. The test subjects were 10 grade II students. Data collection techniques are used validation sheets, interviews, field note sheets. Analysis of the data used to test its validity using Aiken's formula. Based on the results of the analysis, the validity of learning media of 0.78 is included in the valid category. Based on the results of the analysis, it was concluded that the audio virtual learning media developed already met the criteria for valid and effective learning tools.